An investigation into the relationship between tolerance of ambiguity and creativity among military officers - McClary, Rob B. (Kansas State University, 2009)
This study investigated the relationship between the tolerance of ambiguity (AT) levels of the officers attending the U.S. Army’s School of Advanced Military Studies (SAMS) and the creativity of the military plans they developed. Located aboard Fort Leavenworth, KS, SAMS is an Army school providing education to specially selected officers in preparation for duties in positions as battalion commanders and lead planners for Army divisions and corps. The officers at SAMS are grouped into seminars for their classes, and they remain with their seminars throughout the yearlong educational program. The twin purposes of this study were to (a) test for the relationship between AT and creativity suggested by various theories of creativity and (b) contribute to the Army’s efforts to increase the creativity of its officers by empirically identifying the expected positive correlation between the officers AT levels and the creativity of their plans. A sample of 66 officers participated in the study. They each independently developed a military plan in response to a common notional scenario. Subsequently they each independently completed the short version of Norton’s (1975) MAT-50 to measure their levels of AT. Their plans were assessed for creativity using Amabile’s Consensual Assessment Technique (CAT). The high inter-rater reliability among the judges (r = .82) demonstrated the effectiveness of the CAT as a method for assessing the creativity of military plans. Counter to the expectation, analysis of the data revealed a small negative correlation throughout the sample between AT scores and the creativity of the plans, producing a disconfirmation dilemma for the researcher. Analysis revealed that the sample’s collective levels of AT differed among the various subscales of the MAT-50. Additionally, post hoc analysis revealed statistically significant variance of the creativity of the officers’ plans between the different seminars to which they were assigned. In the seminar with the highest creativity scores, there was a small positive correlation between AT and creativity, while in the seminar with the lowest creativity scores, there was a medium sized negative correlation between the two variables. Implications of these findings and recommendations for future research are discussed.
Keywords: Creativity; Tolerance of ambiguity; Education, Adult and Continuing (0516); Psychology, Cognitive (0633)